2010
DOI: 10.1038/pj.2010.74
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a photocrosslinkable hyperbranched polyester containing methacryloyl groups by the reaction of 1,4-bis(chloromethyl)benzene with 1,3,5-benzenetricarboxylic acid followed by reaction with methacrylic acid

Abstract: The synthesis and photo-polymerization of hyperbranched polyesters (HBPEs) containing terminal methacryloyl groups (HBPE-MA) were examined. Polycondensations of 1,4-bis(chloromethyl)benzene with 1,3,5-benzenetricarboxylic acid using 1, 8-diazabicyclo[5.4.0]undec-7-ene as a base were performed to give the soluble HBPEs in satisfactorily high yields. Furthermore, HBPE-MA was synthesized by the reaction of HBPE with methacrylic acid. The photo-induced radical polymerization of HBPE-MA was performed in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Further, the A n + B m ‐type method has significant advantages for industrial applications, because commercially available monomers can be used, and soluble hyperbranched polymer can be synthesized in high yield by control of the polymerization conditions, such as monomer feed ratio, monomer concentration, and reaction time. Many hyperbranched polymers have been reported: hyperbranched polyamide, hyperbranched polyesters, hyperbranched polyimide, hyperbranched polybenzoxazole, and hyperbranched polyacetal . Very recently, Ramakrishnan et al reported the synthesis of a photodegradable hyperbranched polyacetal by means of an AB 2 ‐type method.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the A n + B m ‐type method has significant advantages for industrial applications, because commercially available monomers can be used, and soluble hyperbranched polymer can be synthesized in high yield by control of the polymerization conditions, such as monomer feed ratio, monomer concentration, and reaction time. Many hyperbranched polymers have been reported: hyperbranched polyamide, hyperbranched polyesters, hyperbranched polyimide, hyperbranched polybenzoxazole, and hyperbranched polyacetal . Very recently, Ramakrishnan et al reported the synthesis of a photodegradable hyperbranched polyacetal by means of an AB 2 ‐type method.…”
Section: Introductionmentioning
confidence: 99%
“…But the toxic reagent is not good to operator and environment. The reaction with carboxyl groups catalyzed by DBU as a base is also common with short reaction time, simple postprocessing, high selectivity and yield, but the side chain such as hydroxyl would affect the selectivity 21 .…”
Section: Introduction Of C=cmentioning
confidence: 99%